PENGARUH PROFITABILITAS, SALES GROWTH, LIKUIDITAS, DAN LEVERAGE TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2018 – 2020 - Gilbert Jacob Ratuela; Lintje Kalangi; Jessy D. L. Warongan (Universitas Sam Ratulangi, 2022)
This study aims to determine and analyze the effect of Profitability, Sales Growth, Liquidity, Leverage, on Financial Distress in manufacturing companies listed on the Indonesia Stock Exchange. This research is a quantitative research by processing secondary data in the form of annual reports of manufacturing companies. The sampling of this research was carried out using the purposive sampling method, namely the selection of samples at random, but using certain considerations and criteria set by researchers in the Manufacturing sector companies listed on the IDX in 2018-2020 with a total of 165 samples of observations.The data analysis used in this study is multiple linear regression analysis. The results obtained indicate that profitability and liquidity have a negative and significant effect on financial distress, also sales growth has a negative but not significant effect, while leverage has a positive and significant effect on financial distress. This means, if leverage increases, financial distress will also experience a significant increase and vice versa.